2003
DOI: 10.1038/sj.bjp.0705007
|View full text |Cite
|
Sign up to set email alerts
|

5‐hydroxyindole causes convulsions and increases transmitter release in the CA1 region of the rat hippocampus

Abstract: 1 5-hydroxyindole (5-OHi) is a proposed tryptophan metabolite able to cause convulsions when systemically injected into rodents. We studied its e ects using microdialysis in vivo and electrophysiological approaches in vitro. 2 Local administration of 5-OHi into the CA1 region of the rat hippocampus, via a microdialysis probe, signi®cantly increased glutamate concentrations in the dialysates. 3 In rat hippocampal slices, using extracellular recordings in the CA1 region, 5-OHi (30 ± 300 mM) increased the amplitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 39 publications
4
19
0
Order By: Relevance
“…Since the 5HI + 4OH-GTS-21 mediated increase in EPSC frequency was blocked with TTX but unchanged by MLA, our data suggest these effects were not mediated by direct activation of α7 nAChRs, but rather by increases in action potential-dependent transmitter release. This is consistent with studies that have shown 5-HI mediated increases in glutamate release, the amplitude of population spikes, and the amplitude of evoked excitatory postsynaptic potentials in the hippocampus (Mannaioni et al, 2003). However, to our knowledge, this is the first report showing that 5-HI potentiates the frequency of spontaneous EPSCs in CA1 pyramidal cells.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Since the 5HI + 4OH-GTS-21 mediated increase in EPSC frequency was blocked with TTX but unchanged by MLA, our data suggest these effects were not mediated by direct activation of α7 nAChRs, but rather by increases in action potential-dependent transmitter release. This is consistent with studies that have shown 5-HI mediated increases in glutamate release, the amplitude of population spikes, and the amplitude of evoked excitatory postsynaptic potentials in the hippocampus (Mannaioni et al, 2003). However, to our knowledge, this is the first report showing that 5-HI potentiates the frequency of spontaneous EPSCs in CA1 pyramidal cells.…”
Section: Discussionsupporting
confidence: 92%
“…However, 5-HI also produces a number of other physiological effects. For example, in the hippocampus 5-HI increases glutamate release, the amplitude of population spikes, and the amplitude of evoked excitatory and inhibitory postsynaptic potentials (Mannaioni et al, 2003). Also, 5-HI increases the frequency and amplitude of spontaneous GABAergic inhibitory postsynaptic currents (IPSCs) (Mannaioni et al, 2003;Mok and Kew, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5-HT 3 receptor is not only the target of the natural agonist 5-HT but also a variety of allosteric modulators including the 5-HT analog 5-hydroxyindole (5-HI). Both 5-HT and 5-HI are metabolites of tryptophan (Mannaioni et al, 2003). 5-HI has been shown to increase release of neurotransmitter in the cerebellum and hippocampus (Zwart et al, 2002;Mannaioni et al, 2003) and triggers convulsion in rats (Mannaioni et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Both 5-HT and 5-HI are metabolites of tryptophan (Mannaioni et al, 2003). 5-HI has been shown to increase release of neurotransmitter in the cerebellum and hippocampus (Zwart et al, 2002;Mannaioni et al, 2003) and triggers convulsion in rats (Mannaioni et al, 2003). 5-HI is a positive modulator of the 5-HT 3 receptor (Kooyman et al, 1993;van Hooft et al, 1997;Gunthorpe & Lummis, 1999) and α7 nicotinic acetylcholine receptor (Zwart et al, 2002;Selina Mok & Kew, 2006).…”
Section: Introductionmentioning
confidence: 99%